Regulatory T cells sense effector T-cell activation through synchronized JunB expression - Wu, Jingxia; Ma, Sicong; Hotz-Wagenblatt, Agnes; Angel, Peter; Mohr, Kerstin; Schlimbach, Tilo; Schmitt, Michael; Cui, Guoliang (FEBS letters, 2019)
To maintain immune tolerance, effector T-cell (Teff) responses must be checked by the regulatory T cells (Tregs) in time. It remains incompletely understood how Tregs sense real-time Teff activation. Here, we report that the AP-1 transcription factor JunB, which is induced in Teffs upon T-cell receptor (TCR) activation, is also increased in Tregs by TCR stimuli. Treg-specific deletion of Junb impairs Treg identity, causes uncontrolled inflammatory cytokine production by Teffs and leads to the T-box transcription factor T-bet-dependent spontaneous inflammation. Furthermore, JunB deficiency in Tregs unleashes antitumor Teff responses in a mouse model of melanoma. We conclude that JunB alarms Tregs of the emerging Teff activation and synchronizes immune regulation with the immune reaction in autoimmunity and cancer.
Gesehen am 30.07.2019